A unique mitigator sequence determines the species specificity of the major late promoter in adenovirus type 12 DNA. - Zock, C (1993)
Human adenovirus type 12 (Ad12) cannot replicate in hamster cells, whereas human cells are permissive for Ad12. Ad12 DNA replication and late-gene and virus-associated RNA expression are blocked in hamster cells. Early Ad12 genes are transcribed, and the viral DNA can be integrated into the host genome. Ad12 DNA replication and late-gene transcription can be complemented in hamster cells by E1 functions of Ad2 or Ad5, for which hamster cells are fully permissive (for a review, see W. Doerfler, Adv. Virus Res. 39:89-128, 1991). We have previously demonstrated that a 33-nucleotide mitigator sequence, which is located in the downstream region of the major late promoter (MLP) of Ad12 DNA, is responsible for the inactivity of the Ad12 MLP in hamster cells (C. Zock and W. Doerfler, EMBO J. 9:1615-1623, 1990). A similar negative regulator has not been found in the MLP of Ad2 DNA. We have now studied the mechanism of action of this mitigator element. The results of nuclear run-on experiments document the absence of MLP transcripts in the nuclei of Ad12-infected BHK21 hamster cells. Surprisingly, the mitigator element cannot elicit its function in in vitro transcription experiments with nuclear extracts from both hamster BHK21 and human HeLa cells. Intact nuclear topology and/or tightly bound nuclear elements that cannot be eluted in nuclear extracts are somehow required for recognition of the Ad12 mitigator. Electrophoretic mobility shift assays have not revealed significant differences in the binding of proteins from human HeLa or hamster BHK21 cells to the mitigator sequence in the MLP of Ad12 DNA or to the corresponding sequence in Ad2 DNA. We have converted the sequence of the mitigator in the MLP of Ad12 DNA to the equivalent sequence in the MLP of Ad2 DNA by site-directed mutagenesis. This construct was not active in hamster cells. When the Ad12 mitigator, on the other hand, was inserted into the Ad2 MLP, the latter's function in hamster cells was not compromised. Deletions in the 5' upstream region of the Ad12 MLP have provided evidence for the existence of additional sequences that codetermine the deficiency of the Ad12 MLP in hamster cells. The amphifunctional YY1 protein from HeLa cells can bind specifically to the mitigator and to upstream elements of the MLP of Ad12 DNA.(ABSTRACT TRUNCATED AT 400 WORDS)